2023
DOI: 10.1002/mnfr.202200711
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet Alleviates Hypoglycemia‐Induced Neuroinflammation via Modulation the Gut Microbiota in Mice

Abstract: Scope: This study aims to investigate the role of gut microbiota regulation with ketogenic diet (KD) in hypoglycemia-induced neuroinflammation. Methods and results: Immunofluorescence staining and western blotting show that KD alleviates blood-brain barrier injury induced by hypoglycemia by increasing Podxl and zonula occludens-1 (ZO-1) levels. KD-fed mice show reduced brain edema by decreasing aquaporin-4 (AQP4) content and maintaining its polarized expression. 16S rRNA gene amplicon sequencing results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Three hours after injection, all groups were administered 0.1 mL of 50% glucose by gavage for rescue, followed by resuming the same diet as before. 14…”
Section: Animals Diets and Experimental Setupmentioning
confidence: 99%
“…Three hours after injection, all groups were administered 0.1 mL of 50% glucose by gavage for rescue, followed by resuming the same diet as before. 14…”
Section: Animals Diets and Experimental Setupmentioning
confidence: 99%
“…Metabolic signaling pathways (such as mTOR, AMPK, and HIF-1 pathways) and metabolites (lactate, glutamine, arginine), such as the activation of the mTOR and AMPK pathways, have been shown to influence macrophage polarization. [10] As metabolic reprogramming towards other pathways might lead to the differentiation of diverse phenotypes and even dysfunction of macrophages in health and disease, [25] it has been suggested that reprogramming the metabolism of macrophages could represent a promising therapeutic strategy for several diseases. [26,27] Due to the ability to induce metabolic reprogramming, energy restriction is considered to have the potential to regulate macrophage function.…”
Section: Fasting-mimicking Dietsmentioning
confidence: 99%
“…[7] These include alterations in energy metabolism, regulation of glucose and growth factor levels in the blood, [6] reduction of ROS production and related cell damage, [4] induction of autophagy [8] and DNA repair, [9] and modulation of the gut microbiota. [10] Given the reliance on immune cell function, maintenance, and clonal expansion on metabolism, energy restriction has the potential to shape and modulate the immune response. [11] It has become increasingly evident that macrophages, a type of innate immune cell distributed throughout the body, play critical roles in mediating the outcome of CR/fasting in various diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Since the 1960s, there have been 1200-3000 clinical studies investigating treatments for neuroinflammatory diseases. Combinations of anti-inflammatory drugs, [9][10][11] antioxidants, [12][13][14] corticosteroids, 15,16 exercise, [17][18][19] and tailored diets [20][21][22][23][24] have been implemented with limited long-term success. While these strategies can help manage disease symptoms, they fail to fully resolve inflammation within the CNS.…”
Section: Introductionmentioning
confidence: 99%